AN EXAMPLE OF SEQUENCE OF BLASCHKE PRODUCTS WHICH CONVERGE UNIFORMLY AT A UNIT DISC - Nastovski, Ljupčo (Matematichki Bilten, 2002)
The question of existence of sequence of Blaschke products which uniformly converges on the whole unit disk \(D={z:|z|<1}\) is an important one. So, in this paper it is given an example of sequence of Blaschke products which uniformly converges on the whole unit disk \(D={z:|z|<1}\) and even more whose boundary value is Blaschke product.